2018
DOI: 10.1055/s-0038-1675418
|View full text |Cite
|
Sign up to set email alerts
|

Cooled Radio Frequency Ablation for the Treatment of Osteoarthritis-Related Knee Pain: Evidence, Indications, and Outcomes

Abstract: Knee osteoarthritis (OA) is a common condition associated with pain and physical impairment in a large segment of the population. The traditional treatment algorithm progresses from conservative modalities to nonsurgical options to surgical intervention. Surgical intervention often provides reliable pain relief but not all patients are surgical candidates and there are some patients who prefer not to have surgery. Cooled radio frequency ablation (C-RFA) is a treatment with the potential to provide pain relief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Cooled radiofrequency ablation (CRFA) has been shown to provide at least 12 months of relief for painful conditions of the spine, and has recently emerged as a minimally invasive option for pain control in patients with OA of the knee . An initial report by Bellini suggested CRFA can provide 12 months of analgesia when used in this patient population .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooled radiofrequency ablation (CRFA) has been shown to provide at least 12 months of relief for painful conditions of the spine, and has recently emerged as a minimally invasive option for pain control in patients with OA of the knee . An initial report by Bellini suggested CRFA can provide 12 months of analgesia when used in this patient population .…”
Section: Introductionmentioning
confidence: 99%
“…5 Cooled radiofrequency ablation (CRFA) has been shown to provide at least 12 months of relief for painful conditions of the spine, [6][7][8][9][10] and has recently emerged as a minimally invasive option for pain control in patients with OA of the knee. 11 An initial report by Bellini suggested CRFA can provide 12 months of analgesia when used in this patient population. 12 A prospective, multicenter randomized study involving 151 subjects with chronic knee pain (≥6 months) compared CRFA to IAS injection for pain management.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors may influence the outcomes of diagnostic genicular blocks, that include patient selection, fluid volume and anatomical considerations [34,35]. A newer anatomical study of the anterior knee joint capsule showed a complicated frequency map in 15 dissected knees and suggested that the larger lesion may overcome variability of nerve location and possibly influence clinical outcomes [35].…”
Section: Patient Selection Considerations and Predictors Of Treatment Successmentioning
confidence: 99%
“…8 CRFA of joint-specific sensory nerves has been shown to provide at least 12 months of relief for painful conditions of the spine, [9][10][11] and has gained recognition as a minimally invasive treatment option for pain associated with knee OA. 12 A prospective, multicenter, randomized, crossover trial involving 151 subjects with chronic knee pain (duration ≥6 months) unresponsive to conservative modalities compared CRFA of genicular nerves to a single IAS injection: at 6 months post intervention, 74% of CFRA subjects reported ≥50% reduction in pain from baseline compared to just 16% in the IAS group (p < 0.0001); 13 at 12 months post intervention, 65% of CRFA subjects maintained ≥50% pain relief, with a mean overall reduction of 4.3 Numeric Rating Scale (NRS) points from baseline (p < 0.0001) and substantial functional improvements. 14 The sustained benefits of genicular CFRA observed by Davis et al 14 prompted the investigators to enroll CFRA subjects from the 12-month controlled trial in an observational extension study, the results of which showed sustained pain relief and functional improvements persisting to 18 and 24 months after CRFA.…”
Section: Introductionmentioning
confidence: 99%